The future of the aeronautics: 360º reskilling and upskilling approach - Aguiar, B.; Pinto, M.; Rosa, M.; Oliveira, S.; Maio, C. (9th European Conference for Aeronautics and Space Sciences (EUCASS), 2022)
The solution to challenges in aeronautics involves shifting traditional learning and development into reskilling and upskilling. However, some see it as a responsibility of industries, others as a responsibility of educational institutes, and some others as a responsibility of workers themselves. We review each stakeholder’s role, importance, and actions to take, applied to the aeronautics sector. The pathway to overcome the skills challenge is through an interconnected action, where all stakeholders work in synergy, and consider other pressing challenges, such as age/gender inclusion, with benefits for both single business growth and for prosperity of Aeronautics in post-covid times.